The Use of Wayground Platform in Teaching Japanese Vocabulary in Kaiwa Course for Japanese Language Education Study Program Students - Wuisang, Justien R.R.; Komarudin, Mochamad Arief (KIRYOKU, 2026)
This study aims to analyze the effectiveness of using the Wayground digital quiz platform in teaching Japanese vocabulary in the Kaiwa course for students of the Japanese Language Education Study Program at the Faculty of Language and Arts, Universitas Negeri Manado. This study used a mixed-methods approach. The subjects were 32 second-semester students in the 2024-2025 academic year. Data collection was conducted through interviews, documentation, and objective tests. The results showed that the use of the Wayground digital platform increased learning motivation and material comprehension, with the success rate reaching 81% for the class. Out of 32 students, 7 students achieved a score of 100%, 6 students achieved 96%, 7 students achieved 76%, 5 students achieved 72%, 4 students achieved 68%, 1 student achieved 60%, and the lowest scores of 50% and 38% were achieved by 1 student each. The analysis shows that there is an increase in the accuracy of vocabulary mastery after using Wayground. However, some students require additional support due to limited digital literacy, technical issues, and connectivity constraints. This study highlights the importance of integrating technology with hands-on guidance to improve students' learning motivation and vocabulary acquisition, which in turn will improve their Japanese speaking ability.